NEW ANTIBIOTICS FROM GENETICALLY ENGINEERED ACTINOMYCETES: I. 2-NORERYTHROMYCINS, ISOLATION AND STRUCTURAL DETERMINATIONS - GREENER, KEVIN D.; MCALPINE, JAMES B.; TUAN, JAMES S.; KATZ, LEONARD; WHITTERN, DAVID N.; BUKO, ALEX; BROWN, DAVID P. (Journal of antibiotics, 1987)
Novel macrolide antibiotics have been isolated from a genetically manipulated actinomycete. The major components produced have been isolated and identified as 2-norerythromycins A, B, C and D by mass spectrometry and extensive ID and 2D NMR experiments.